The Influence of Television User Satisfaction on Youtube Media Adoption in the Cipanas Kabar Facebook Group - Andriani, Astri Dwi; Anggawan, M. Yusuf Agam; Kurniadi, Endrian (MultiTech Publisher, 2023)
TV The presence of the internet provides an additional medium for receiving various information. One of these media is Youtube. This study aims to examine the effect of television user satisfaction on the adoption of Youtube media in the Facebook group Kabar Cipanas. The method used in this research is quantitative method. The theory used in this research is the Uses and Gratifications theory by Katz, Blumer and Gurevitch and the innovation diffusion theory by Evert M. Rogers and Floyd G. Shoemaker. The data testing technique was carried out using IBM SPSS Statistics 22 (64-bit edition) 2013 software. The results of this study indicate that TV user satisfaction has a significant effect (0.006) on the adoption of Youtube Media in members of the Facebook group Kabar Cipanas